The Dynamics of the Relationship Between Government and Citizens from the Perspective of Administrative Court Decisions: Dinamika Hubungan antara Pemerintah dan Warga Negara dalam Perspektif Keputusan Tata Usaha Negara - Aldri Frinaldi; Roberia; Angga Putra Tri Rezeki (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The relationship between the government and citizens within the realm of administrative law often encounters tensions, particularly when State Administrative Decisions (Keputusan Tata Usaha Negara/KTUN) fail to embody principles of justice and the protection of rights. This study aims to explore the dynamics of this relationship by analyzing academic literature related to KTUN. The research employs a systematic literature review combined with a bibliometric approach using 176 journal articles sourced from Google Scholar. Overlay visualization analysis was conducted through VOSviewer software to identify thematic trends and keyword co-occurrence. The results reveal that terms such as e-government, authority, and state administrative decision dominate recent academic discourse, indicating the growing relevance of digital governance and administrative accountability. The study finds that the effectiveness of KTUN is closely linked to its legal validity, institutional accountability, and the extent of public participation in administrative processes. This research highlights a critical gap in how KTUN is formulated and implemented in practice, suggesting that existing administrative legal frameworks may lack responsiveness to evolving societal needs. The novelty of this study lies in its bibliometric-based mapping of current academic perspectives on KTUN, which provides a clearer understanding of emerging patterns and theoretical directions in the field. The study recommends strengthening adaptive legal frameworks in state administration that are more participatory and responsive to societal transformations, thereby improving the quality of public decisions and governance outcomes in Indonesia.